Critical Analysis of Covid-19 in Sikkim as On - Bhutia, Sonam; Kakoti, Bibhuti Bhusan (Asian Journal of Pharmaceutical Research and Development, 2020)
Objective: The goal of this current short communication research was to critically analysis and systematically collect data during this pandemic situation, government strategies and their implementation to counter the pandemic virus-Novel COVID-19 within the Sikkim state and its border areas. Methods: It highlighted data obtained by the different agencies prvided by government and independent media houses. Here we highlighted data focused on factors such Home quarantin, Facility Quarantine, Triage facility, details of patients admitted, Logistic supplies and details of test for COVID-19. Result: Total cumulatative number of passengers screened were 6,03,370 at the major entrance(Rangpo check post), persons in home quarantine, Triage facility, total number of sample sent for examination and total number of sample found positive and found negative were 2954, 2, 59, 0 and 59 respectively till dated:11/04.2020. Conclusion: With the State Government's bold move towards mandatory quarantine of the population inside the state for total 40 days lockdown (including both 1st phase and 2nd phase). Sikkim reports zero COVID-19 positive cases as on 19/04/2020. These statistics are first of its kind for the communication and to keep the scientific evidence for future knowledge.